2022
DOI: 10.1093/jpids/piac044
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Intussusception in Bamako, Mali, Before and After the Introduction of Rotavirus Vaccine

Abstract: Pentavalent rotavirus vaccine has been associated with a small increase in intussusception, but pre- and post-introduction data are lacking in many low-resource settings. Using chart review and prospective surveillance data, intussusception incidence was estimated in Bamako, Mali. The mean annual intussusception incidence post-introduction was not significantly different from that of pre-introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…Although RV1 and RV5 were both found to be associated with a slightly elevated risk of intussusception within 1-7 days after vaccination, [12][13][14] To date, the incidence rate of intussusception for children aged <1 year after introduction of the RV vaccine has been evaluated in several countries (see Table 3). [20][21][22][23] Similar to the findings of the present study, a decreased incidence of intussusception after RV vaccine introduction was reported in Taiwan (82.2-68.7 per 100 000 infants from the pre-to post-vaccine era) and in Korea (241.7-177.3 per 100 000 infants from the pre-to post-vaccine era). 20,21 By contrast, the incidence of intussusception did not change significantly…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although RV1 and RV5 were both found to be associated with a slightly elevated risk of intussusception within 1-7 days after vaccination, [12][13][14] To date, the incidence rate of intussusception for children aged <1 year after introduction of the RV vaccine has been evaluated in several countries (see Table 3). [20][21][22][23] Similar to the findings of the present study, a decreased incidence of intussusception after RV vaccine introduction was reported in Taiwan (82.2-68.7 per 100 000 infants from the pre-to post-vaccine era) and in Korea (241.7-177.3 per 100 000 infants from the pre-to post-vaccine era). 20,21 By contrast, the incidence of intussusception did not change significantly…”
Section: Discussionsupporting
confidence: 89%
“… 20–23 Similar to the findings of the present study, a decreased incidence of intussusception after RV vaccine introduction was reported in Taiwan (82.2–68.7 per 100 000 infants from the pre‐ to post‐vaccine era) and in Korea (241.7–177.3 per 100 000 infants from the pre‐ to post‐vaccine era) 20,21 . By contrast, the incidence of intussusception did not change significantly following RV vaccine introduction in Canada or in Mali 22,23 . The reported RV vaccination rate during the study period was approximately 50% in both Japan and Taiwan, whereas this rate was over 80% in Mali; thus, it is difficult to compare the differences in intussusception incidence rates because of the large differences in RV vaccination rates 24 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Whether differences in factors such as genetics, diet or environment could explain this increased risk remains unclear. However, the differences in the frates of ISN by ethnicity could possibly be explained by low socioeconomic status [ 72 ], difference in access to health care or lack of accessibility to medical treatment [ 73 ], health care-seeking behavior [ 74 ] or lack of awareness among parents when their child presents with symptoms of ISN leading them to seek medical attention [ 75 ]. ISN classically presents in an infant or toddler with sudden onset of intermittent, severe and progressive abdominal pain, accompanied by inconsolable crying often with vomiting, palpable sausage-shaped abdominal mass, red currant jelly stools, anorexia, dehydration, irritability, abdominal tenderness, lethargy and pallor [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%